DETERMINAN HIPERTENSI MASYARAKAT PESISIR DI KABUPATEN JEMBER - Yuliana Amelia Reza Mustofa; Candra Bumi (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
Hypertension is abnormal blood pressure. High blood pressure is often called the silent killer because this disease shows no warning. There are 2 factors cause increased morbidity and mortality rates due to hypertension, namely, factors that can be modified, such as obesity, sodium consumption, smoking, alcohol consumption, education, and employment. Factors that cannot be changed include age, gender, and family history. This study aimed to identify the determinants of hypertension in coastal communities in the working area of ​​the Cakru Community Health Center, Jember Regency. This type of research is analytic, using a cross-sectional research design. The number of samples in this study reached 111 respondents. The results of statistical analysis research using the Chi-square test showed statistical significance, namely the gender variable p-value0.032, POR= 2.478, 95%CI (1.151 – 5.336) family history p-value0.001, POR= 4.248, 95%CI (1.898 – 9.509) work p-value0.040, POR= 2.393, 95%CI (1.109 – 5.162) obesity p-value0.000, POR= 5.614, 95%CI (2.440 – 12.916) and sodium p-value0.000 POR= 10.500 95%CI (4.342 – 25,389) associated with hypertension. The results of the logistic regression analysis show that the variable that has the most influence on coastal communities in the working area of ​​the Cakru Community Health Center, Jember Regency, is sodium, which has a sig value of 0.000. The conclusion showed, there was a relationship with the variables of gender, family history, occupation, obesity, and sodium to the incidence of hypertension, and the variable that most influences the incidence of hypertension in this study is sodium.